PHILOSOPHY ANALYSIS OF THE ROLE OF PASTORS AND PARENTS IN EDUCATING CHILDREN AND YOUTH AGGARES ON EDUCATIONALLEVEL IN CHURCH BASED ON 22: 6 IN GMAHK-7 JEMAAT PADASUKA CIMAHI, BANDUNG - Josua Siahaan; Stimson B. Hutagalung (Fakultas Filsafat Universitas Advent Indonesia, 2019)
The author examines